Manajemen Strategi Gereja dalam Penginjilan Perkotaan - Deisy Agustina Tinangon; Beni Chandra Purba (JUITAK: Jurnal Ilmiah Teologi dan Pendidikan Kristen, 2024)
Evangelism is a command that comes directly from the mouth of Jesus Christ. The command to evangelize Matthew 28:19-20 was implemented by the Apostles in all places, both villages and cities. This is motivated by the command itself "all nations" meaning anyone, anywhere, and at any time. In general, the definition of an urban area is a residential area that includes a main city and is supported by peripheral areas that support the main city. Urban areas are also more complex areas than rural areas. Financial turnover in the economy is very fast. Generally the population has sufficient education. A more comprehensive way of thinking and unique characteristics due to busy work, even seem selfish and indifferent. All of this shows the need for the church to carry out its own strategic management in carrying out urban evangelism. Researchers used qualitative methods based on library research. Data that already exists will be lifted and become the wealth of this writing. The aim of this writing is to add to the richness of existing writings. Furthermore, it can be applied according to the needs and demands of urban evangelism.